Rome power & glory : the rise - Townsley, Graham; Fields, Ed.; Westbrook, Joel.; Coyote, Peter; Discovery Channel (Firm). ([S.l.] Discovery Communications, 1998)
"Rome's dream of greatness was a prelude to a nightmare. It was not for another 100 years that the state would mature and commit to one enduring view of itself. It would be the army, more than any other force, that was destined to shape Rome's lasting identity"--Container.
Produced by Alexandria Productions, Inc. for TLC.
Distributed in the Philippines by MagnaVision.
Executive producers, Ed Fields and Joel Westbrook ; series producer, Graham Townsley ; associate producers, Neil Barrett, Elizabeth Olson, Richard A. Roughton and Holly Sniff ; narrator, Peter Coyote.
Keywords: Rome (Italy) -- History; Rome -- Army -- History; Mediterranean Region -- History